2018
DOI: 10.1016/j.ssmph.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Long-run effects of early childhood exposure to cholera on final height: Evidence from industrializing Japan

Abstract: Pandemic cholera is one of the most topical and urgent issues in many developing countries. However, although a growing body of research has shown the negative long-run effects of infectious disease exposure on human health, the long-run influences of early childhood exposure to cholera have thus far been understudied. To bridge this gap in the body of knowledge, we draw both on new data describing adult height from 1899 to 1910 from comprehensive official Japanese army records and on data recording the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Our findings on the positive long-lasting impacts of paid maternity leave are consistent with studies showing the importance of early-life circumstances to long-term outcomes. Specifically, early-life exposure to negative shocks such as poverty and disease could leave irreversible consequences on cognitive development, health, and productivity in adulthood (Alderman et al, 2006;Almond, 2006;Duncan et al, 2010;Ogasawara and Inoue, 2018). In another vein, the results of our study are also in line with those highlighting the link between prenatal conditions and after-birth outcomes Nguyen, 2020, 2021).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings on the positive long-lasting impacts of paid maternity leave are consistent with studies showing the importance of early-life circumstances to long-term outcomes. Specifically, early-life exposure to negative shocks such as poverty and disease could leave irreversible consequences on cognitive development, health, and productivity in adulthood (Alderman et al, 2006;Almond, 2006;Duncan et al, 2010;Ogasawara and Inoue, 2018). In another vein, the results of our study are also in line with those highlighting the link between prenatal conditions and after-birth outcomes Nguyen, 2020, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Grasgruber et al (2014) demonstrate that early-nutrition levels, especially the consumption of high-quality proteins, can explain most of the differences in adult height. Incidences of major diseases during childhood and the prenatal period can also depress educational attainment and also adult stature as infections might take away nutrients and inflammatory diseases might thwart the growth of long bones (Almond, 2006;Batty et al, 2009;Herzog et al, 2014;Ogasawara and Inoue, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The seminal study of Almond ( 2006 ) finds that in utero exposure to the 1918 influenza pandemic had long-term negative effects in terms of education attainment, physical disability, income and socioeconomic status. Closely related to our study, Ogasawara and Inoue ( 2018 ) and Ritter ( 2020 ) find negative long-term effects of prenatal exposure to the cholera epidemic among adults in Japan and Peru, respectively. A relatively smaller number of studies have shown that in utero shocks may have an effect on postnatal childhood mortality.…”
Section: Introductionsupporting
confidence: 86%
“… 6 In the late nineteenth-century Japan, cholera epidemic were not likely to affect the size of birth cohort or the risk of fetal deaths ( Ogasawara and Inoue, 2018 ). Thus, the potential mortality selection effects could be negligible.…”
mentioning
confidence: 99%